The Influence of Budget Planning, Procurement of Goods or Services, and Budget Implementation on Budget Absorption (Case Study at the Regional Secretariat of West Java Province) - David Pratama Putra; Purwanto Purwanto (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2025)
Budget absorption is an important indicator in measuring the effectiveness of regional financial management. However, at the Regional Secretariat of West Java Province, budget absorption still exhibits a “slow and back-loaded” pattern, where expenditures tend to accumulate at the end of the fiscal year. The diminished absorption rate is conjectured to be shaped by several pivotal determinants within the fiscal administration continuum, namely financial schematization, acquisition of goods/services, and fiscal execution. Deficient planning manuscripts, procrastination in procurement procedures, and aberrations in budgetary enforcement are presumed to constitute principal impediments to the maximization of fiscal absorption. This paper seeks to scrutinize the ramifications of financial schematization, goods/services acquisition, and fiscal execution upon budgetary absorption, both in isolated and conjoint modalities. A quantitative paradigm was adopted, employing a survey mechanism facilitated through the dissemination of questionnaires. A cohort of 63 informants was delineated via purposive sampling, with eligibility predicated upon direct participation in the fiscal governance trajectory. The dataset was subjected to multiple linear regression analysis with the assistance of SPSS version 25. The empirical outcomes divulge that all three explanatory variables, financial schematization, goods/services acquisition, and fiscal enactment, exert a positive and statistically consequential influence on budgetary absorption, both independently and collectively. The adjusted R² statistic of 0.611 demonstrates that the constructed model elucidates 61.1% of the variance in fiscal absorption. These revelations corroborate Agency Theory, accentuating the salience of accountability and the execution of fiduciary mandates by agents (the governing apparatus) in service of principals (the public).